Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1007/s00381-001-0547-y
|View full text |Cite|
|
Sign up to set email alerts
|

Pediatric brain tumors: statistics of SNUH, Korea (1959–2000)

Abstract: The relative incidences of germ cell tumors, neuronal tumors, and oligodendroglial tumors increased after the introduction of magnetic resonance imaging (MRI). In contrast, the incidence rates of medulloblastomas and ependymal tumors decreased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
50
5
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 16 publications
14
50
5
1
Order By: Relevance
“…While in Korea the mean age was 7.8 [15], and in Iranian study, it was 8.8 [1]. However, in the present study, the age at diagnosis had a peek at 11 years.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…While in Korea the mean age was 7.8 [15], and in Iranian study, it was 8.8 [1]. However, in the present study, the age at diagnosis had a peek at 11 years.…”
Section: Discussioncontrasting
confidence: 71%
“…This slight prevalence of males over females reflects the gender distribution of the population at risk, the same was found in a Kuwaiti study [13], where male slight preponderance was reported. In another study [14], where the male-tofemale ratio was 1:3, indicated that the pediatric brain tumors were more prevalent in males than in females and other studies found that too [1,15,18].…”
Section: Discussionmentioning
confidence: 94%
“…[13][14][15][16] The CBTC collected data on 3291 children with CNS brain tumors. These patients received first tumor surgery at one of the CBTC centers before January 1, 1979 before age 21 years.…”
Section: Discussionmentioning
confidence: 99%
“…In the recently reported series of primary pediatric brain tumors in children, supratentorial tumors predominated over infratentorial tumors. 14,16,17 By using chi-square test, statistical comparison of relative incidence of tumors in these series was performed (data not shown). Except choroid plexus tumor and pineal parenchymal tumor, significant statistical difference (P Ͻ 0.05) of relative incidence existed in astrocytic tumor, medulloblastoma, germ cell tumor, craniopharyngioma, ependymoma, and oligodendroglioma.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have shown higher rates of intracranial GCTs in Asians compared with those in the Western population (Cho et al, 2002; Committee of Brain Tumor Registry of Japan 2003; Wong et al, 2005;Park et al, 2008). However, a recent report indicates that Japan has a similar rate of intracranial GCTs as does the United States (McCarthy et al, 2012).…”
Section: Introductionmentioning
confidence: 98%